Does spatial heterogeneity blur the signature of dispersal syndromes on spatial patterns of woody species? A test in a tropical dry forest - Escudero, A. (2017)
Spatial patterns of adult plants are a consequence of several ecological processes related to seed dispersal and recruitment. Dispersal limitation, mediated by dispersal syndrome, is considered a key factor in the formation of adult plant spatial patterns. Although this initial pattern determined by dispersal has been thoroughly studied, the subsequently modification by the effect of additional ecological factors, such as habitat heterogeneity is less understood. We explored the relative importance of dispersal syndrome and spatial heterogeneity on the realization of spatial patterns of adult trees in an Ecuadorian tropical dry forest. The spatial distribution of 28 species was modeled with four different spatial point processes each: homogeneous Poisson (HPP), inhomogeneous Poisson (IPP), homogeneous Poisson cluster (HPCP), and inhomogeneous Poisson cluster process (IPCP). These models allowed us to discern between effects of random processes, habitat heterogeneity, limited dispersal, and joint effects of habitat heterogeneity and limited dispersal. We employed Akaike's information criterion (AIC) to select the model which best fit the spatial pattern of each species. The best model of each species was used to analyze differences in cluster size and degree of aggregation, between dispersal syndromes. Seventy-five percent of the species showed inhomogeneous patterns. IPCP yielded the best fit for the spatial distribution of 50% of species in the studied forest and was the prevalent model for the three dispersal syndromes. Thus, the effect of spatial heterogeneity was prevalent in the distribution of most species in this dry tropical forest. Only 21% of species had spatial patterns compatible with random mechanisms associated to limited dispersal around parent sources. Clearly, ignoring habitat heterogeneity could bias the analysis of relationships between dispersal syndrome and species patterns.